Lower Ionospheric Turbulence Variations During the Recent Activity of Etna’s Volcano, Sicily, in December 2018 - Contadakis, Michael E.; Arabelos, Demeter; Scordilis, Emmanuel (Bulletin of the Geological Society of Greece, 2019)
In this paper, we present an investigation on the ionospheric turbulence from TEC observations before and during the recent activity of Etna’s Volcano. Mount Etna is located close to the eastern coast of Sicily. The last eruption of Etna volcano took place on 24 December 2018 while two days later (26 December, 02:19 UTC) an earthquake of M=5.0 occurred 15 km to the ESE of the volcano, causing damage to the nearby city of Catania. The results of our investigation, on the occasion of the Etna’s Volcanic activity, indicate that the high-frequency limit fo of the ionospheric turbulence band content, is increasing with time to the volcano eruption while, at the same time, fo isdecreasing with distance from the volcano. We conclude that the LAIC mechanism through acoustic or gravity waves could explain this phenomenology, as it has happened in cases of earthquake activity. Our observations indicate that the effect of volcanic eruption on the band content of the ionospheric turbulence is insignificant at distances greater than 1000km (at the most), a fact that we must consider in our research on Ionospheric turbulence in relation to earthquake precursors research.